2023
DOI: 10.3390/ijms25010501
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Metabolism Regulators Are the Possible Determinant for Characteristics of Myopic Human Scleral Stroma Fibroblasts (HSSFs)

Hiroshi Ohguro,
Araya Umetsu,
Tatsuya Sato
et al.

Abstract: The purpose of the current investigation was to elucidate what kinds of responsible mechanisms induce elongation of the sclera in myopic eyes. To do this, two-dimensional (2D) cultures of human scleral stromal fibroblasts (HSSFs) obtained from eyes with two different axial length (AL) groups, <26 mm (low AL group, n = 2) and >27 mm (high AL group, n = 3), were subjected to (1) measurements of Seahorse mitochondrial and glycolytic indices to evaluate biological aspects and (2) analysis by RNA sequencing. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 64 publications
1
0
0
Order By: Relevance
“…Accompanying sclera remodeling, dramatic thinning of the choroid is associated with reduced vision in myopic patients. Till now, the most common mechanism of sclera remodeling was the decrease of choroidal blood perfusion and metabolism alteration of the fundus resulting from it . Since hypoxia can cause extensive changes in cellular material metabolism, differences in metabolic characteristics have already been observed, including lipid metabolism, cholesterol metabolism, glutamic acid metabolism, and carbohydrate metabolism in myopic eyes. Our study revealed a similar tendency that cellular metabolic processes changed significantly in myopic aqueous humor, including the l -ascorbic acid metabolic process, the lipoprotein catabolic process, and the hyaluronan metabolic process with the highest enrichment score. These results indicate that, under hypoxic circumstances in the myopic fundus, there are also distinctive metabolic and structure-related alterations in the aqueous humor.…”
Section: Discussionsupporting
confidence: 67%
“…Accompanying sclera remodeling, dramatic thinning of the choroid is associated with reduced vision in myopic patients. Till now, the most common mechanism of sclera remodeling was the decrease of choroidal blood perfusion and metabolism alteration of the fundus resulting from it . Since hypoxia can cause extensive changes in cellular material metabolism, differences in metabolic characteristics have already been observed, including lipid metabolism, cholesterol metabolism, glutamic acid metabolism, and carbohydrate metabolism in myopic eyes. Our study revealed a similar tendency that cellular metabolic processes changed significantly in myopic aqueous humor, including the l -ascorbic acid metabolic process, the lipoprotein catabolic process, and the hyaluronan metabolic process with the highest enrichment score. These results indicate that, under hypoxic circumstances in the myopic fundus, there are also distinctive metabolic and structure-related alterations in the aqueous humor.…”
Section: Discussionsupporting
confidence: 67%